Regime change in Kyrgyzstan and the specter of coups in the CIS - Uwe Halbach; Franz Eder (Stiftung Wissenschaft und Politik (SWP), 2005)
The developments in Kyrgyzstan differ markedly from the regime changes in Georgia and Ukraine. Yet the overthrow of Askar Akayev's regime again raises the question of how 'contagious' changes of government are in the Commonwealth of Independent States (CIS). The forms of political power that have become established in this region range from 'managed democracies' to authoritarian presidential regimes and neo-totalitarian systems. Sovereignty is centered largely in the person of the president, not in the will of the electorate. Since rigged elections were the catalyst for peaceful regime change in Georgia and Ukraine, speculation about the likely next candidate for a 'democratic coup' shifted to countries where elections were scheduled and there existed at least the rudiments of a civil society and a politically interested public. The message went out from Tbilisi and Kiev that electoral fraud was a risky business for the powers-that-be in any system that was at least partly pluralistic. President Akayev's reaction to this message, long before the recent parliamentary elections in his country, showed that he was most unsettled. (SWP-Comments / SWP)
Keywords: 320